2022
DOI: 10.3847/1538-4357/ac4bd8
|View full text |Cite
|
Sign up to set email alerts
|

Electron-scale Current Layers in the Martian Magnetotail: Spatial Scaling and Properties of Embedding

Abstract: Current sheets (CSs) are widespread objects in space plasma capable of storing and, then, explosively releasing the accumulated magnetic energy. In planetary magnetotails the cross-tail CS plays an important role in the global dynamics of the tail and in the transformation of the magnetic energy into the kinetic and thermal energies of the ambient plasma. We have analyzed 114 crossings of the cross-tail CS by the MAVEN spacecraft at X MSO ∼ [−1.0, −2.8]R M. Magnetic field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For strong anisotropy 𝐴𝐴 𝐴𝐴𝑎𝑎 = 1 (this is the marginal fire hose condition discussed by (Burkhart et al, 1992), we get the singular case 𝐴𝐴 𝐴𝐴𝑥𝑥 ( z𝑧) ∼ z𝑧1∕3 and current 𝐴𝐴 𝐴𝐴𝑦𝑦 for 𝐴𝐴 𝐴𝐴= 0 formally becomes infinite. There is nothing dramatic in it because this singularity is integrable and STCSs with such 𝐴𝐴 𝐴𝐴( z𝑧) profile were found earlier in the Martial magnetotail (Grigorenko et al, 2019(Grigorenko et al, , 2022Zelenyi et al, 2020) 42, although data on anisotropy were available only within the narrow range of parameters ( 𝐴𝐴 𝐴𝐴𝑎𝑎 ≤ 0.2 ). Correspondingly, all STCSs in our analysis have the usual linear 𝐴𝐴 𝐴𝐴( z𝑧) ∼ z𝑧 profile as was predicted by our theory.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For strong anisotropy 𝐴𝐴 𝐴𝐴𝑎𝑎 = 1 (this is the marginal fire hose condition discussed by (Burkhart et al, 1992), we get the singular case 𝐴𝐴 𝐴𝐴𝑥𝑥 ( z𝑧) ∼ z𝑧1∕3 and current 𝐴𝐴 𝐴𝐴𝑦𝑦 for 𝐴𝐴 𝐴𝐴= 0 formally becomes infinite. There is nothing dramatic in it because this singularity is integrable and STCSs with such 𝐴𝐴 𝐴𝐴( z𝑧) profile were found earlier in the Martial magnetotail (Grigorenko et al, 2019(Grigorenko et al, , 2022Zelenyi et al, 2020) 42, although data on anisotropy were available only within the narrow range of parameters ( 𝐴𝐴 𝐴𝐴𝑎𝑎 ≤ 0.2 ). Correspondingly, all STCSs in our analysis have the usual linear 𝐴𝐴 𝐴𝐴( z𝑧) ∼ z𝑧 profile as was predicted by our theory.…”
Section: Discussionmentioning
confidence: 91%
“…For strong anisotropy βa=1 ${\beta }_{a}=1$ (this is the marginal fire hose condition discussed by (Burkhart et al., 1992), we get the singular case Bxtrueztruez1/3 ${B}_{x}\left(\tilde{z}\right)\sim {\tilde{z}}^{1/3}$ and current jy ${j}_{y}$ for z=0 $z=0$ formally becomes infinite. There is nothing dramatic in it because this singularity is integrable and STCSs with such Btruez $B\left(\tilde{z}\right)$ profile were found earlier in the Martial magnetotail (Grigorenko et al., 2019, 2022; Zelenyi et al., 2020) but in more general case βa<1 ${\beta }_{a}< 1$ this singularity disappears and Le1βa ${L}_{e}\sim 1-{\beta }_{a}$ linearly grows with the decrease in βa ${\beta }_{a}$. Magnetic field for these cases has already the usual linear magnetic profile: Bxtrueztruez1βa ${B}_{x}\left(\tilde{z}\right)\sim \frac{\tilde{z}}{1-{\beta }_{a}}$.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since charged particles have a physical scale of gyration or diffusion in the electromagnetic field, the dynamic evolution of the CS strongly depends on its spatial scale. Observational events suggested that the thickness of the Martian magnetotail CS is comparable to, and sometimes even less than, the proton scale (Grigorenko et al., 2019, 2022; Harada et al., 2015, 2020). Theoretically, when the CS becomes thinner than the proton inertial length, multiple X‐line magnetic reconnection can be triggered (Fujimoto, 2006; Huang et al., 2011; Paschmann et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…scale (Grigorenko et al, 2019(Grigorenko et al, , 2022Harada et al, 2015Harada et al, , 2020. Theoretically, when the CS becomes thinner than the proton inertial length, multiple X-line magnetic reconnection can be triggered (Fujimoto, 2006;Huang et al, 2011;Paschmann et al, 2013).…”
mentioning
confidence: 99%